Knowledge and Social Relevance: Analyzing Socio-scientific Nature of Learning Competencies and Standards in Grade 8 Science - Purisima, Jasper Kent A.; Celedonio, Milagros A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The Philippine education system is obscured of global competence by various challenges including developing skills and inclusive education (Diano, et. al, 2023). Since 2018, the Philippines has placed at the bottom, ranking last out of 78 participants, and barely improved in 2022 ranking 77th out of 81 countries participating (Education GPS & OECD, n.d.; OECD, 2022). A study revealed that essential competencies in the curriculum should highlight various concepts and contexts of problems in the community (Belmi & Mangali, 2020). Through a quantitative research design, this study analyzed 40 stratified samples of competencies and standards of the Grade 8 Science Curriculum Guide for its distribution and extent of socio-scientific issues (SSI) consideration and the underlying factors that could potentially hinder its effective implementation in the four (4) science disciplines. Findings revealed an unequal distribution of consideration in the curriculum guide for SSI in different science disciplines. Earth and Space with a mean of 4.26 appear to integrate SSI more effectively as compared to other science disciplines. On the other hand, varying factors such as limitations to various resources and socio-cultural contexts could largely hinder the implementation and integration of SSI in the curriculum guide. This study concludes that there is sufficient and acceptable frequency in the distribution of SSI in the curriculum guide of Science Grade 8 across four core disciplines, however, this study also acknowledges that there are present limitations that need to be considered.